(untitled) (Eurasian Journal of Humanities and Social Sciences, 2021)
Nag is considered to be a spiritual rise in the development, prospect, prosperity of a state and society, a place among the most developed countries of the world - educated, highinfellektual potential, connected with young people who embodied noble qualities in their hearts and minds, mature in all respects, a sitki for the fate of vatan sincerely serving, bringing the faithful generation to adulthood, at the same time it imposes a responsible task. Preservation of mother and Child Health in our country, raising the younger generation spiritually and competently is one of the priority tasks. As soon as the child was born, giving him education became a higher goal.The institution, previously called kindergarten, is today recognized as a pre-school educational institution.Buildings are gaining modern outfits. Special attention is paid to the teaching of foreign languages in preschool institutions, the organization of sports and artistic circles in order to educate the younger generation healthy, morally and morally. Therefore, one of the main goals is to educate children who have a high intellectual potential and are able to speak freely in foreign languages. In this article, opinions and comments are made about the processes of formation of pre-school children’s abilities through innovative technologies.